Analysis Of The Relationship Of Covid-19 Vaccination Status With Hematological Features In Pregnant Women - Helena Rugun Nauli Nainggolan; Leo Jumadi Simanjuntak; Gerald Osson Fransiska Siahaan (Jurnal EduHealth, 2023)
Background:Pregnant women are a group that is vulnerable to being infected with Covid-19, and this has an impact on increasing the risk of maternal outcomes with Covid-19. According to the Indonesian government's policy, pregnant women can be given Covid-19 vaccinations, including the Pfizer and Moderna mRNA platforms, and the Sinovac inactivated platform vaccine. Pregnant women who have been vaccinated against Covid-19 will be less likely to suffer from Covid-19, thereby reducing the risk of complications for the mother and baby. Hematology images can assess prognosis, and predict and monitor the course of disease due to Covid-19. Purpose:To determine the relationship between Covid-19 vaccination status and the average levels of hemoglobin, platelets, leukocytes, lymphocytes, and the ratio of neutrophils to lymphocytes in women giving birth at Herna Hospital and Mitra Sejati Hospital, Medan. Methods: The research design used was descriptive-analytical with a cross-sectional approach used to analyze the relationship between Covid-19 vaccination status and the hematological features of third-trimester pregnant women who will give birth by cesarean section. This research was carried out at Herna General Hospital and Mitra Sejati Hospital in Medan. The inclusion criteria were full-term pregnancy, no complications during pregnancy, and willing to take part in the research and the exclusion criteria were unclear Covid-19 vaccination status. Analysis of the research data with the Chi-square test. Results:Based on the research results, from 190 samples of pregnant women, there were no significant differences in vaccination status based on hematological parameters, age, and gravida. Conclusion: Based on the research results, it can be concluded that there is no relationship between Covid-19 vaccination status and hematological features in pregnant women.